The limits of public authority in issuing administrative decisions in Algeria - Frodjen, Taieb; Louglaib, Saad; Abdelhamid, Ben Rahmoune (The International tax journal, 2025)
The issuance of administrative decisions by the public authority is an important manifestation of the exercise of its assigned functions, which are aimed at achieving public interests for the benefit of society. This responsibility is undertaken by the public authority in Algeria. However, the issuance of administrative decisions is subject to limits and regulations aimed at protecting the rights of individuals and the community, while also ensuring that the authority fulfils its duties within the framework of the law. These limits are founded on legal and judicial rules, which are provided by administrative and judicial oversight.